Report on industrial attachment on spray coating of buffer layer for CIGS application - Ouyang, Xin (2015)
As one of the mainstream thin film photovoltaic devices, copper indium gallium selenide (CIGS) has significant advantages over other PV competitors. Firstly, CIGS has a high absorption coefficient value of 105/cm2 and a spectral response of 300nm-1300nm, much wider as compared to silicon cells (400-700nm), leading to longer effective time for sun light harvesting everyday. Secondly, CIGS does not have the problem of light-induced degradation, which exists in silicon cells; whereas, it exhibits improving performance over the first few days due to “light-soaking” effect [1]. Thirdly, its flexibility and light weight make it particularly favorable for BIPV and portable power application. Lastly, CIGS solar cell requires less material consumption and simpler fabrication process as compared to silicon solar cells.